Bentham's binary form of maximizing utilitarianism. Issue 1 (2nd January 2018) - Gustafsson, Johan E.
ABSTRACT: Jeremy Bentham is often interpreted as defending a satisficing, rather than maximizing, version of utilitarianism, where an act is right as long as it produces more pleasure than pain. This lack of maximization is surprising given Bentham's maximizing slogan 'the greatest happiness of the greatest number'. Against the satisficing interpretation, I argue that Bentham consistently defends a maximizing version of utilitarianism, where an act's consequences are compared to those of not performing the act. I show that following this version of utilitarianism requires that one realizes the greatest happiness for all affected individuals.